A promoter toolbox for tissue-specific expression supporting translational research in cassava (Manihot esculenta) - Zierer, Wolfgang; Anjanappa, Ravi Bodampalli; Lamm, Christian; Chang, Shu-Heng; Gruissem, Wilhelm; Sonnewald, Uwe (Frontiers in Plant Science, 2022)
There is an urgent need to stimulate agricultural output in many tropical and subtropical countries of the world to combat hunger and malnutrition. The starchy crop cassava (Manihot esculenta), growing even under sub-optimal conditions, is a key staple food in these regions, providing millions of people with food. Cassava biotechnology is an important technique benefiting agricultural progress, but successful implementation of many biotechnological concepts depends on the availability of the right spatiotemporal expression tools. Yet, well-characterized cassava promoters are scarce in the public domain. In this study, we investigate the promoter activity and tissue specificity of 24 different promoter elements in stably transformed cassava plants. We show that many of the investigated promoters, especially from other species, have surprisingly low activity and/or tissue specificity, but feature several promoter sequences that can drive tissue-specific expression in either autotrophic-, transport- or storage tissues. We especially highlight pAtCAB1, pMePsbR, and pSlRBCS2 as strong and specific source promoters, pAtSUC2, pMeSWEET1-like, and pMeSUS1 as valuable tools for phloem and phloem parenchyma expression, and pStB33, pMeGPT, pStGBSS1, as well as pStPatatin Class I, as strong and specific promoters for heterotrophic storage tissues. We hope that the provided information and sequences prove valuable to the cassava community by contributing to the successful implementation of biotechnological concepts aimed at the improvement of cassava nutritional value and productivity.
CRIS-Team WoS Importer:2023-01-20

Corrigendum: A promoter toolbox for tissue-specific expression supporting translational research in cassava (Manihot esculenta)(Front. Plant Sci., (2022), 13, (1042379), 10.3389/fpls.2022.1042379) - Zierer, Wolfgang; Anjanappa, Ravi Bodampalli; Lamm, Christian; Chang, Shu Heng; Gruissem, Wilhelm; Sonnewald, Uwe (Frontiers in Plant Science, 2024)
In the published article, there was an error in the legend for Figure 2 and the legend for Figure S2 as published. In the Figure 2 legend, subfigure F2 – F6 were falsely labeled subfigure H2 – H6. In the Figure S2 legend, the subfigures C-F were incorrectly labeled and the labeling for subfigures G-H was missing. The corrected legend appears below. FIGURE 2 Representative GUS staining pattern of at least three events from pAtCAB1, pStLS1, pAtRBCS3B, pMeGBSS1, pStSSS3, and pStSTP1 promoter-reporter plants. pAtCAB1::GUS = A1) Source leaf (Inlay = Close-up), B1) Sink leaf, C1) Emerging leaves, D1) Petiole cross-section, E1) Upper stem cross-section, F1) Lower stem cross-section, G1) Storage root cross-section, H1) Fibrous roots, I1) GUS expression levels of four pAtCAB1::GUS lines relative to three pCaMV35S::GUS lines in %. pStLS1::GUS = A2) Source leaf, B2) Sink leaf, C2) Petiole cross-section, D2) Upper stem cross-section, E2) Storage root cross-section, F2) Fibrous roots. pAtRBCS3B::GUS = A3) Source leaf, B3) Sink leaf, C3) Petiole cross-section, D3) Upper stem cross-section, E3) Storage root cross-section, F3) Fibrous roots. pMeGBSS1::GUS = A4) Source leaf, B4) Sink leaf, C4) Petiole cross-section, D4) Upper stem cross-section, E4) Storage root cross-section, F4) Fibrous roots. pStSSS3::GUS = A5) Source leaf, B5) Sink leaf, C5) Petiole cross-section, D5) Upper stem cross-section, E5) Storage root cross-section, F5) Fibrous roots. pStSTP1::GUS = A6) Source leaf, B6) Sink leaf, C6) Petiole cross-section, D6) Upper stem cross-section, E6) Storage root cross-section, F6) Fibrous roots. Plants were either grown on the field at NCHU experimental station Taichung, Taiwan or in a greenhouse in Erlangen, Germany. Tissues from approximately 3-month-old cassava plants were used. FIGURE S2 Representative GUS staining pattern of three pCaMV35S::GUS promoter-reporter lines. A) Source leaf, B) Sink leaf, C) Emerging leaves, D) Petiole cross-section, E) Upper stem cross-section, F) Lower stem cross-section, G) Storage root cross-section, H) Fibrous roots. The authors apologize for these errors and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.
CRIS-Team Scopus Importer:2024-05-24
Keywords: biotechnology; cassava; parenchyma; phloem; promoter; storage root; tissue; xylem

Efficient sugar utilization and transition from oxidative to substrate-level phosphorylation in high starch storage roots of African cassava genotypes - Lamm, Christian; Rabbi, Ismail Y.; Medeiros, David Barbosa; Rosado-Souza, Laise; Pommerrenig, Benjamin; Dahmani, Ismail; Rüscher, David; Hofmann, Jörg; van Doorn, Anna M.; Schlereth, Armin; Neuhaus, H. Ekkehard; Fernie, Alisdair R.; et al. (Plant Journal, 2023)
Cassava's storage roots represent one of the most important sources of nutritional carbohydrates worldwide. Particularly, smallholder farmers in sub-Saharan Africa depend on this crop plant, where resilient and yield-improved varieties are of vital importance to support steadily increasing populations. Aided by a growing understanding of the plant's metabolism and physiology, targeted improvement concepts already led to visible gains in recent years. To expand our knowledge and to contribute to these successes, we investigated storage roots of eight cassava genotypes with differential dry matter content from three successive field trials for their proteomic and metabolic profiles. At large, the metabolic focus in storage roots transitioned from cellular growth processes toward carbohydrate and nitrogen storage with increasing dry matter content. This is reflected in higher abundance of proteins related to nucleotide synthesis, protein turnover, and vacuolar energization in low starch genotypes, while proteins involved in sugar conversion and glycolysis were more prevalent in high dry matter genotypes. This shift in metabolic orientation was underlined by a clear transition from oxidative- to substrate-level phosphorylation in high dry matter genotypes. Our analyses highlight metabolic patterns that are consistently and quantitatively associated with high dry matter accumulation in cassava storage roots, providing fundamental understanding of cassava's metabolism as well as a data resource for targeted genetic improvement.
CRIS-Team Scopus Importer:2023-07-21
Keywords: energy metabolism; glycolysis; Manihot esculenta; metabolomics; oxidative phosphorylation; proteomics; source/sink; starch metabolism; sugar metabolism; TCA-cycle

Hop/Sti1-A Two-Faced Cochaperone Involved in Pattern Recognition Receptor Maturation and Viral Infection - Lamm, Christian; Kraner, Max; Hofmann, Jörg; Boernke, Frederik; Mock, Hans-Peter; Sonnewald, Uwe (Frontiers in Plant Science, 2017)
Perception of pathogens by host pattern recognition receptors (PRRs) or R proteins is a prerequisite to promote successful immune responses. The Hsp70/Hsp90 organizing protein Hop/Sti1, a multifunctional cochaperone, has been implicated in the maturation of a receptor-like kinase (RLK) necessary for chitin sensing. However, it remains unknown whether Hop/Sti1 is generally participating in PRR genesis. Using RNA-interference (RNAi), we silenced Hop/Sti1 expression in Nicotiana tabacum to gain further insight into the role of the cochaperone in plant defense responses. As expected, transgenic plants do not respond to chitin treatment anymore. In contrast to this, trafficking and functionality of the flagellin PRR FLS2 were unaltered, suggesting a selective involvement of Hop/Sti1 during PRR maturation. Furthermore, Hop/Sti1 was identified as a cellular determinant of Potato virus Y (PVY) symptom development in tobacco, since PVY was able to accumulate to near wild-type level without provoking the usual veinal necrosis phenotype. In addition, typical antiviral host defense responses were suppressed in the transgenic plants. These data suggest that perception of PVY is dependent on Hop/Sti1-mediated receptor maturation, while viral symptoms represent a failing attempt to restrict PVY spread. In addition, Hop/Sti1 colocalized with virus-induced membrane aggregates in wild-type plants. The retention of Hop/Sti1 in potential viral replication complexes suggests a role during viral translation/replication, explaining why RNAi-lines do not exhibit increased susceptibility to PVY. This study provides evidence for a dual role of Hop/Sti1 in PRR maturation and pathogen perception as well as in promoting viral proliferation.
Keywords: Hop/Sti1 cochaperone; pattern recognition receptor; CERK1; FLS2; pathogen perception; Nicotiana tabacum cv. Samsun NN; Potato virus Y

Hop/Sti1 - A Two-Faced Cochaperone Involved in Pattern Recognition Receptor Maturation and Viral Infection. - Lamm, Christian; Kraner, Max; Hofmann, Jörg; Boernke, Frederik; Mock, Hans-Peter; Sonnewald, Uwe (Frontiers in Plant Science, 2017)
Perception of pathogens by host pattern recognition receptors (PRRs) or R proteins is a prerequisite to promote successful immune responses. The Hsp70/Hsp90 organizing protein Hop/Sti1, a multifunctional cochaperone, has been implicated in the maturation of a receptor-like kinase (RLK) necessary for chitin sensing. However, it remains unknown whether Hop/Sti1 is generally participating in PRR genesis. Using RNA-interference (RNAi), we silenced Hop/Sti1 expression in Nicotiana tabacum to gain further insight into the role of the cochaperone in plant defense responses. As expected, transgenic plants do not respond to chitin treatment anymore. In contrast to this, trafficking and functionality of the flagellin PRR FLS2 were unaltered, suggesting a selective involvement of Hop/Sti1 during PRR maturation. Furthermore, Hop/Sti1 was identified as a cellular determinant of Potato virus Y (PVY) symptom development in tobacco, since PVY was able to accumulate to near wild-type level without provoking the usual veinal necrosis phenotype. In addition, typical antiviral host defense responses were suppressed in the transgenic plants. These data suggest that perception of PVY is dependent on Hop/Sti1-mediated receptor maturation, while viral symptoms represent a failing attempt to restrict PVY spread. In addition, Hop/Sti1 colocalized with virus-induced membrane aggregates in wild-type plants. The retention of Hop/Sti1 in potential viral replication complexes suggests a role during viral translation/replication, explaining why RNAi-lines do not exhibit increased susceptibility to PVY. This study provides evidence for a dual role of Hop/Sti1 in PRR maturation and pathogen perception as well as in promoting viral proliferation.

Human Cytomegalovirus Nuclear Egress Proteins Ectopically Expressed in the Heterologous Environment of Plant Cells are Strictly Targeted to the Nuclear Envelope - Lamm, Christian; Link, Katrin; Wagner, Sabrina; Milbradt, Jens; Marschall, Manfred; Sonnewald, Uwe (Viruses, 2016)
In all eukaryotic cells, the nucleus forms a prominent cellular compartment containing the cell's nuclear genome. Although structurally similar, animal and plant nuclei differ substantially in details of their architecture. One example is the nuclear lamina, a layer of tightly interconnected filament proteins (lamins) underlying the nuclear envelope of metazoans. So far no orthologous lamin genes could be detected in plant genomes and putative lamin-like proteins are only poorly described in plants. To probe for potentially conserved features of metazoan and plant nuclear envelopes, we ectopically expressed the core nuclear egress proteins of human cytomegalovirus pUL50 and pUL53 in plant cells. pUL50 localizes to the inner envelope of metazoan nuclei and recruits the nuclear localized pUL53 to it, forming heterodimers. Upon expression in plant cells, a very similar localization pattern of both proteins could be determined. Notably, pUL50 is specifically targeted to the plant nuclear envelope in a rim-like fashion, a location to which coexpressed pUL53 becomes strictly corecruited from its initial nucleoplasmic distribution. Using pUL50 as bait in a yeast two-hybrid screening, the cytoplasmic re-initiation supporting protein RISP could be identified. Interaction of pUL50 and RISP could be confirmed by coexpression and coimmunoprecipitation in mammalian cells and by confocal laser scanning microscopy in plant cells, demonstrating partial pUL50-RISP colocalization in areas of the nuclear rim and other intracellular compartments. Thus, our study provides strong evidence for conserved structural features of plant and metazoan nuclear envelops and identifies RISP as a potential pUL50-interacting plant protein.
Keywords: pUL53; plant cells; nuclear envelope; pUL50; re-initiation supporting protein RISP; human cytomegalovirus

Human promyelocytic leukemia protein is targeted to distinct subnuclear domains in plant nuclei and colocalizes with nucleolar constituents in a SUMO-dependent manner - Lamm, Christian; Scherer, Myriam; Reuter, Nina; Amin, Bushra; Stamminger, Thomas; Sonnewald, Uwe (FEBS Open Bio, 2016)
Eukaryotic nuclei are subdivided into subnuclear structures. Among the most prominent of these structures are the nucleolus and the PML nuclear bodies (PML-NBs). PML-NBs are spherical multiprotein aggregates of varying size localized in the interchromosomal area. PML-NB formation is dependent on the presence of the promyelocytic leukemia protein (PML) as well as on post-translational modification of core components by covalent attachment of the small ubiquitin-like modifier (SUMO). So far, PML-NBs as well as PML have been described in mammalian cells only, whereas no orthologs are known in the plant kingdom. In order to investigate conserved mechanisms in PML targeting, we expressed human PML (hPML) fused to the GFP in Nicotiana benthamiana. Using confocal laser scanning microscopy and coimmunoprecipitation followed by mass spectrometric analysis, we found the fusion protein in association with nucleolar constituents. Importantly, mutants of hPML, which are no longer SUMOylated, showed altered localizations, implying SUMO-dependent targeting of hPML in plants as has previously been shown for mammalian cells. Interestingly, in the presence of proteasome inhibitors, hPML could also be found in the nucleolus of mammalian cells suggesting conserved targeting mechanisms of PML across kingdoms. Finally, Solanum tuberosum COP1, a proposed PML-like protein from plants, was fused to the red fluorescent protein (RFP) and coexpressed with hPML::eGFP. Microscopic analysis confirmed the localization of COP1::RFP in nuclear speckles. However, hPML::eGFP did not colocalize with COP1::RFP. Hence, we conclude that plants do not possess specialized PML-NBs, but that their functions may be covered by other subnuclear structures like the nucleolus.
Keywords: nucleolus; plant subnuclear structures; promyelocytic leukemia protein; nuclear bodies; small ubiquitin like modifier

Symplasmic phloem unloading and radial post-phloem transport via vascular rays in tuberous roots of Manihot esculenta - Mehdi, Rabih; Lamm, Christian; Bodampalli Anjanappa, Ravi; Müdsam, Christina; Saeed, Muhammad; Klima, Janine; Kraner, Max; Ludewig, Frank; Knoblauch, Michael; Gruissem, Wilhelm; Sonnewald, Uwe; Zierer, Wolfgang (Journal of Experimental Botany, 2019)
Cassava (Manihot esculenta) is one of the most important staple food crops worldwide. Its starchy tuberous roots supply over 800 million people with carbohydrates. Yet, surprisingly little is known about the processes involved in filling of those vital storage organs. A better understanding of cassava carbohydrate allocation and starch storage is key to improving storage root yield. Here, we studied cassava morphology and phloem sap flow from source to sink using transgenic pAtSUC2::GFP plants, the phloem tracers esculin and 5(6)-carboxyfluorescein diacetate, as well as several staining techniques. We show that cassava performs apoplasmic phloem loading in source leaves and symplasmic unloading into phloem parenchyma cells of tuberous roots. We demonstrate that vascular rays play an important role in radial transport from the phloem to xylem parenchyma cells in tuberous roots. Furthermore, enzymatic and proteomic measurements of storage root tissues confirmed high abundance and activity of enzymes involved in the sucrose synthase-mediated pathway and indicated that starch is stored most efficiently in the outer xylem layers of tuberous roots. Our findings form the basis for biotechnological approaches aimed at improved phloem loading and enhanced carbohydrate allocation and storage in order to increase tuberous root yield of cassava.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Apoplast; cassava; CFDA; esculin; morphology; phloem; ray; starch; SUC2; symplast